Faktor-faktor yang Mempengaruhi Independensi Penampilan Akuntan Publik (Survei pada Kantor Akuntan Publik dan Pemakai Laporan Keuangan di Surabaya) - Wati, Christina; Subroto, Bambang (TEMA, 2003)
The objective of this study is to identify and to test factors affecting public accountants’s appearance. In this study, six factors are identified to have some influence on the independence. These factors are: financial interest in the client’s company and business relationship with their clients, nonaudit services performed by auditors, the tenure of an audit firm with a given client, competition in providing auditing services among auditors, the size of the audit firm, and audit fee. Based on questionnaire received from 64 respondents from public accounting firms, go public companies, banks, and brokers in Surabaya, the result showed that the magnitude of auditor’s independence impaired is influenced by financial interest in the client’s company and business relationship with their clients, the tenure of an audit firm with a given client, and audit fee. The data were analysed using proportion and chi-square technique. The following sequence of the factors reflect the magnitude of each factor in influencing the impairment of independence: 1) financial interest in the client’s company and business relationship with their clients (75,0%), 2) the tenure of an audit firm with a given client (67,2%), 3) the larger of audit fee (57,8%), 4) competition on providing auditing services among auditors (40,6%), 5) nonaudit services performed by auditors (39,5%), 6) the smaller audit firms (18,0%). To avoid the impairment of the auditors’ independence in appearance, the following actions are recommended: (a) public accounting firms should not angage in financial commitments with the client’s company and in business ventures with the clients, (b) public accounting profession should consider the possibility of partner’s rotation, and peer review, (c) public accounting firms should diversify their clients and services so that a large part of their revenues does not come from a single client, (d) the Honorary Board of the Indonesian Accountant’s Institute should do a strong control the adherence to the code of professional ethics so that unfair competition among the public accounting firms can be avoided. Keywords: auditor’s, independence in appearance, financial interest in the client business relationship, tenure of an audit firm, audit fee.